2009
DOI: 10.1603/008.102.0214
|View full text |Cite
|
Sign up to set email alerts
|

Female Recognition and Sexual Dimorphism of Cuticular Hydrocarbons in Monochamus galloprovincialis (Coleoptera: Cerambycidae)

Abstract: Monochamus galloprovincialis Olivier (Coleoptera: Cerambycidae) is the European vector of the pine wilt nematode, Bursaphelenchus xylophilus (Steiner and Buhrer) Nickle, which causes the pine wilt disease. A series of experiments were carried out to determine the existence of a contact pheromone on the female's cuticle. All males tested tried to copulate with freshly killed females, but none tried to copulate with the same females after they had been washed with hexane. When the hexane extract was reapplied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
(35 reference statements)
2
15
0
3
Order By: Relevance
“…The latter also may play a role in attracting females at relatively short range, as in the Y-tube bioassays reported by Ibeas et al (2008), and even in recognition of males by females. Finally, the chemicallymediated reproductive behavior of M. galloprovincialis is completed when males recognize mates by contact chemoreception of female cuticular compounds (Ibeas et al 2009). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter also may play a role in attracting females at relatively short range, as in the Y-tube bioassays reported by Ibeas et al (2008), and even in recognition of males by females. Finally, the chemicallymediated reproductive behavior of M. galloprovincialis is completed when males recognize mates by contact chemoreception of female cuticular compounds (Ibeas et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Ibeas et al (2008) described the mating behavior of M. galloprovincialis in the laboratory and proposed a chemically-mediated sex recognition by males through the contact of the female elytra with the labial and/or maxillary palpi of the mouthparts. Later, the role of female cuticular compounds in mate recognition was demonstrated, and significant differences between the global hydrocarbon profiles of males and females were found, indicating that females have a contact pheromone on their cuticle that stimulates male copulatory behavior (Ibeas et al 2009). Ibeas et al (2008) also showed that mature female M. galloprovincialis were strongly attracted to mature males feeding on pine shoots in an olfactometer.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that ALB males produce pheromone following attraction to hosts containing virgin females, and that the pheromone acts over a relatively short range, such as within the tree or up to several meters from the male. In both strategies, the chemically mediated reproductive behaviors are completed by contact chemoreception of female cuticular compounds and mating (Allison et al , 2004; Ginzel et al , 2006; Lacey et al , 2008a; Fonseca & Garbin 2009; Ibeas et al , 2008, 2009). Exceptions include the old‐house borer, Hylotrupes bajulus , which utilizes dead wood (Reddy et al , 2005a,b, 2007), and P. californicus , which appears to be unique in its use of a pheromone gland on the ovipositor (Barbour et al , 2006; Cervantes et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Following this model, monochamol may mediate the attraction of the sexes to the larval host and once on the host, contact pheromones on the female cuticle may mediate reproductive isolation. Although contact pheromones have not been identified from females of any Monochamus spp., behavioral studies suggest their existence in M. alternatus (Kim et al 1992), M. galloprovincialis (Ibeas et al 2008, 2009) and M. saltuarius (F.) (Kim et al 2006). …”
Section: Discussionmentioning
confidence: 99%